Konsep Pendidikan Dalam Perspektif Filsafat Islam Menurut Pemikiran Al-Farabi dan Relevansinya di Era Moderen - M. Rafi Alfazri; Intan Probowati; Herlini Puspika Sari (Reflection : Islamic Education Journal, 2024)
This study aims to explore the relevance of Al-Farabi's thought in the context of modern education, with an emphasis on the integration of moral and spiritual values in the curriculum. The method used in this research is descriptive qualitative analysis with a library research approach. The results show that Al-Farabi's educational thought is still very relevant in creating individuals who are noble and active in society, especially amid the negative impact of globalization. It is emphasized that education should focus on character development, spirituality, and ethical understanding, in line with the goals of Islamic education. This research recommends that educators incorporate moral and spiritual values in the contemporary curriculum to produce intellectual and moral individuals, and face the challenges of an increasingly complex age.